If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + (2x + -3) = -1x Reorder the terms: 12 + (-3 + 2x) = -1x Remove parenthesis around (-3 + 2x) 12 + -3 + 2x = -1x Combine like terms: 12 + -3 = 9 9 + 2x = -1x Solving 9 + 2x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 9 + 2x + x = -1x + x Combine like terms: 2x + x = 3x 9 + 3x = -1x + x Combine like terms: -1x + x = 0 9 + 3x = 0 Add '-9' to each side of the equation. 9 + -9 + 3x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 0 + -9 3x = 0 + -9 Combine like terms: 0 + -9 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 3x^2-6y-39=0 | | 2x^2-2x-24=0 | | 3x^2-18x-39=0 | | 3x^2-18x+-9=0 | | (1/2x^5)6 | | 10y=-8x+5 | | -25=9+7(c-5) | | -2.30-0.60y=1.4 | | 2/9-8n^2 | | cos(2x)-3cos(x)+4=0 | | 20x-12y=28 | | 6s*39=141 | | 5x+13=6x | | 6s+39=141 | | 3(x+5)+2(x-3)=0 | | 2(1-4x)=-2(x+3)-4 | | 2-8x=-2x-6-4 | | -2.3+x=5.9 | | 2x+19=90 | | 1/2(16-x)=-12(x*7) | | 0.8x+y=5.4 | | x+54+x+67=113 | | 4(-5)+7= | | x+54=x+67 | | 7/9*x=7/8 | | 188=2(x-6) | | 188=2(x+6) | | 5x/3=30/6 | | 1/3times3/5 | | 4+5x=56 | | rx+1=3y | | 24x-15+2x=29 |